Functional characterization of two paralogs that are novel RNA binding proteins influencing mitochondrial transcripts of Trypanosoma brucei - Kafková, Lucie (Jihočeská univerzita, 2012)
The function of two subunits of the putative mitochondrial RNA binding complex (MRB1) associated with RNA editing in parasitic protist Trypanosoma brucei was studied using various in vivo and in vitro methods of molecular biology.
Functional characterization of two paralogs that are novel RNA binding proteins influencing mitochondrial transcripts of Trypanosoma brucei
Keywords: RNA editing; RNA binding protein; Ribonuclear protein (RNP); mitochondria; trypanosome; RNA editing; RNA binding protein; Ribonuclear protein (RNP); mitochondria; trypanosome